Plataforma para desenvolvimento de registro eletrônico pessoal na área médica (PDRP): o uso das competências para uma PDRP inovadora - Fabrício Pelucci Machado (2018)
Medical practice is a complex activity, involving knowledge of the physician, his ability and the application of these according to the patient's illness and the context in which it is inserted. To assist the professional, the medical record is an essential tool; nevertheless belongs to the institution so that the patient's information is fragmented in each medical service. In order to unify and empower the patient, a personal health record was created with the purpose of maintaining the patient's own health history and serving as a longitudinal database. There has been little progress since the systems are created by computer teams, without the participation of doctors and patients. It is proposed to create an innovative platform model for the development of electronic personal medical record (PDRP), through the use of competencies, which are knowledge and skills applied in a context. Individual and innovation competencies were used. Despite being employed only at the nosocomial level, the context chosen was the hospital, a place where competencies are required. This environment, however, presents a fragmented structure that is not flexible and which makes it difficult to communicate between doctor and patient and among professionals. A theoretical-methodological model was developed, followed by a qualitative research with semi-structured and recorded interviews. In the study, doctors and patients were questioned about the current medical record as well as the competencies to create the PDRP. After content analysis, the model was enriched with the perceptions and competencies indicated by the doctors and patients. The main competencies cited were: autonomy, responsibility, communication, motivation, teamwork.